Venous thromboembolism in patients hospitalized for hip joint replacement surgery. Issue 190 (June 2020) - Keller, Karsten; Hobohm, Lukas; Barco, Stefano; Schmidtmann, Irene; Münzel, Thomas; Engelhardt, Martin; Goldhofer, Markus; Konstantinides, Stavros V.; Drees, Philipp
Abstract: Background: Venous thromboembolism (VTE) is a potentially life-threatening disease. Major transient risk factors include trauma, surgery, and immobilization. Patients undergoing hip joint replacement (HJR) are characterized by a high risk of postoperative VTE, but data on the time trends of VTE rates in this population are sparse. Methods: In an analysis of the German nationwide inpatient sample, we included all hospitalizations for elective primary HJR in Germany from 2005 to 2016. Time trends of the surgical procedure, overall death rates, and VTE rates were analysed, and predictors of VTE identified. Results: Overall, 1, 885, 839 inpatients with elective primary HJR (59.1% women, 51.4% ≥70 years) were included in the analysis. During hospitalization, VTE was documented in 11, 554 (0.6%) patients. While total numbers of primary HJR increased from 145, 223 in 2005 to 171, 421 in 2016 (β-(slope)-estimate 1818 [95%CI 1083 to 2553], P < 0.001), in-hospital VTE decreased from 1288 (0.9%) to 843 (0.5%) cases (β-estimate −0.71 [95%CI -0.77 to −0.65], P < 0.001), and in-hospital death rate from 0.33% (476 deaths) to 0.29% (498 deaths) (β-estimate −0.11 [95%CI -0.20 to −0.02], P = 0.018). Infections during hospitalization were associated with higher VTE risk than cancer and cardiovascular events. VTE events were independently associated with an increased death risk (OR 15.19 [95%CI 14.19–16.86], P < 0.001). Conclusions: While total numbers of HJR increased significantly in Germany between 2005 and 2016, in-hospital rates of VTE decreased from 0.9% to 0.5%. Patients with perioperative VTE had a 15-fold increase of in-hospital death. Cancer, cardiovascular disease and perioperative infections were associated with higher risk for VTE. Highlights: Number of hip joint replacements increased significantly over the past 12 years in Germany. Rate of VTE in these patients decreased from 0.9% in 2005 to 0.5% in 2016. VTE in patients with hip joint replacements increase in-hospital mortality substantially. VTE events prolonged hospitalization duration significantly.